Environmental and health impacts of urban sanitation services in Côte d’Ivoire - Parfait, K.; Kouassi, D.; Hung Nguyen-Viet; Zurbrugg, C.; Bonfoh, Bassirou; Jean, B. (2013)
Equitable access to urban sanitation services is necessary for populations’ welfare and well-being and is one of the Millennium Development Goals. This study highlights how the lack of access to urban waste management infrastructure and services impacts human health and the environment.